An Analysis of Informal Reasoning Fallacy and Critical Thinking Dispositions among Malaysian Undergraduates - Ramasamy, Shamala (ERIC, 2011)
In this information age, the amount of complex information available due to technological advancement would require undergraduates to be extremely competent in processing information systematically. Critical thinking ability of undergraduates has been the focal point among educators, employers and the public at large. One of the dimensions of critical thinking is informal fallacy. Informal fallacy is able to distract us in thinking critically because they tend to appear as reasonable and their unreliability is not apparent on the surface. Empirical research affirms that critical thinking involves cognitive skills and dispositions. Critical thinking dispositions and informal reasoning fallacy are integral in facilitating students to have high ability in thinking critically. The aim of this paper is to measure the level of critical thinking ability among Malaysian undergraduates through the use of informal logic and critical thinking dispositions. A cross sectional survey was conducted on 189 samples of undergraduates from three different disciplines, testing them on newly developed Informal Reasoning Fallacy Instrument (IRFI) and California Critical Thinking Dispositions (CCTDI). A high reliability was achieved from both tests, with Cronbach alpha .802 for IRFI and .843 for CCTDI. Both tests projected good results among Malaysian undergraduates.